1996
DOI: 10.1152/ajpheart.1996.270.4.h1225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ischemia on cerebrovascular responses to N-methyl-D-aspartate in piglets

Abstract: We examined the effects of total global ischemia on cerebral arteriolar responses to N-methyl-D-aspartate (NMDA) in anesthetized newborn pigs. Arteriolar responses to 10(-4) M NMDA were determined before and after 10 to 20 min of ischemia caused by increasing intracranial pressure. Before ischemia, NMDA dilated arterioles by 30 +/- 5% (baseline = 88 +/- 2 microns; n = 6). However, after 10 min of ischemia, arteriolar dilation was reduced to 10 +/- 3% at 1 h (P < 0.05). At 2 and 4 h, NMDA-induced dilation was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
41
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 0 publications
7
41
3
Order By: Relevance
“…In piglets, hypoxia, global ischemia, and asphyxia attenuate NMDA-induced dilation in a dose and timedependent manner (7,12,13) via ROS produced by COX activity (5,35). Endothelial cells are damaged by ischemia (20), but their role in the attenuation of NMDA-induced vasodilation is not supported by the present study.…”
Section: Discussioncontrasting
confidence: 62%
“…In piglets, hypoxia, global ischemia, and asphyxia attenuate NMDA-induced dilation in a dose and timedependent manner (7,12,13) via ROS produced by COX activity (5,35). Endothelial cells are damaged by ischemia (20), but their role in the attenuation of NMDA-induced vasodilation is not supported by the present study.…”
Section: Discussioncontrasting
confidence: 62%
“…Depressed postischemic cerebrovascular dilation is present after global cerebral ischemia (Clavier et al, 1994;Rosenblum and Wormley, 1995;Busija et al, 1996), but less is known about the effects of transient ischemia on microcirculatory response to vasoconstrictors. Our previous studies and those of others show that global ischemic brain injury can attenuate contractile responses to 5-HT (Watanabe et al, 2001;Fadyukova et al, 2004) and to arterial hypercapnia (Nelson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that cerebrovascular responses to exogenous NO remain intact after 10 min of ischemia (13) or 15 min of hypoxia (4), thereby further indicating the neuronal basis for this response. In addition, cortical NO synthase (NOS) activity is not affected by ischemia (13). Therefore, impairment of vasodilation after cerebral ischemia is not due to decreased NOS activity or reduced vascular responsiveness to NO but to a modulation of the response to NMDA at the neuronal level.…”
Section: Discussionmentioning
confidence: 99%
“…However, NMDAinduced arteriolar dilation is highly susceptible to hypoxic or ischemic insults. Thus, even short periods of hypoxia or ischemia dramatically reduce arteriolar dilator responses to NMDA in a dose-and time-dependent manner (4,5,12,13). The mechanisms of impairment of NMDA-induced dilation to hypoxia or ischemia are complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation